2018
DOI: 10.1016/j.jpba.2018.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of corylin in vivo and in vitro

Abstract: Corylin, an phenolic compound from Psoralea corylifolia, has been reported with various pharmacological properties but has poor bioavailability due to massive metabolism. In this study, twelve metabolites of corylin mainly involving in oxidation, hydration, glucuronidation and sulfation were detected in mice. Furthermore, the oxidation and hydration of corylin (M4) in human liver microsomes (HLM) and human intestine microsomes (HIM) were both efficient with high CL (intrinsic clearance) values of 24.29 and 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Flavonoids are abundantly present in plant, fruits and vegetables, and have been indicated to exert several types of anti-inflammatory effects [ 21 , 22 ]. Psoralea corylifolia L. has been widely used as a kidney tonifying herbal medicine for treating many diseases such as osteoporosis [ 23 ], leucoderma and inflammatory diseases of the skin in Asian countries [ 24 ]. Corylin is a main flavonoid that is isolated from Psoralea corylifolia L. Previous studies indicated that corylin has various pharmaceutical effects, including anti-cancer [ 25 , 26 ] and anti-inflammatory properties [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are abundantly present in plant, fruits and vegetables, and have been indicated to exert several types of anti-inflammatory effects [ 21 , 22 ]. Psoralea corylifolia L. has been widely used as a kidney tonifying herbal medicine for treating many diseases such as osteoporosis [ 23 ], leucoderma and inflammatory diseases of the skin in Asian countries [ 24 ]. Corylin is a main flavonoid that is isolated from Psoralea corylifolia L. Previous studies indicated that corylin has various pharmaceutical effects, including anti-cancer [ 25 , 26 ] and anti-inflammatory properties [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…38 In addition, UGT1A1 polymorphisms (1A1*6, 1A1*28) should be investigated to reduce or avoid the dose-limiting toxicities of chemotherapy drugs. 23 In contrast, two-fold higher glucuronidation toward several carcinogenic environmental contaminants was observed in UGT1A9*22/*22 livers compared with UGT1A9*1/*1 and UGT1A9*1/*22 livers. 39 UGT1A10 codon 139 (Glu > Lys) polymorphism exhibited higher catalytic activities against polycyclic aromatic hydrocarbons, and this genotype is most likely an important determinant in the risk for tobaccorelated cancers.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, CYP1A1 and UGT1A10 in extrahepatic tissues (mainly the intestine) as well as CYP1A2 and UGT1A1 mainly in the liver all, accounted for the signicant contributions to the metabolism of PI-103. 23 Apart from the metabolism in the liver and the intestine, the lung and kidney may also participate in its metabolic fate because CYP1A1 is also present in these tissues, and UGT1A9 is mainly expressed in the kidney. 24 Therefore, the metabolic roles of the lung and kidney should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I metabolism and glucuronidation are essentially incubation assays performed routinely in our laboratory. 11,25,30 The incubation system for phase I metabolism included contained Tris-HCl buffer (50 mM, pH ¼ 7.4), MgCl 2 (5 mM), substrates (bavachinin, or specic substrate for each CYP enzyme), enzyme materials (HLM, HIM, animal liver microsomes, or CYP enzymes). The reaction was initiated by addition of NADPH (1 mM) aer a pre-incubation at 37 C for 5 min.…”
Section: Incubation Systems For Phase I Metabolism and Glucuronidationmentioning
confidence: 99%
“…Of these, metabolism (phase I and II reactions) participated more in determining drug exposure at target sites (pharmacodynamics) and toxicity proles (detoxication). 10,11 Isomerization, glucuronidation, sulfonation, hydroxylation, and reduction were considered as the main metabolic pathways in rat samples and rat liver microsomes. 12,13 Poor bioavailability (5.27-36.39%) 13,14 and low plasma concentration (2.13-908.8 ng mL À1 ) [13][14][15][16][17][18] were mainly attributed to massive metabolism aer oral administration of bavachinin or bavachinin-containing extracts.…”
Section: Introductionmentioning
confidence: 99%